2010
DOI: 10.1038/emboj.2010.225
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock factor 1 ameliorates proteotoxicity in cooperation with the transcription factor NFAT

Abstract: Heat shock transcription factor 1 (HSF1) is an important regulator of protein homeostasis (proteostasis) by controlling the expression of major heat shock proteins (Hsps) that facilitate protein folding. However, it is unclear whether other proteostasis pathways are mediated by HSF1. Here, we identified novel targets of HSF1 in mammalian cells, which suppress the aggregation of polyglutamine (polyQ) protein. Among them, we show that one of the nuclear factor of activated T cells (NFAT) proteins, NFATc2, signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 67 publications
6
88
2
Order By: Relevance
“…To clarify whether low expression levels of Hsf-1 have a causative role in the accumulation of pathogenic AR in vivo, we depleted Hsf-1 in AR-97Q mice by crossing them with heterozygous Hsf-1-knockout mice 33 . As Hsf-1-null AR-97Q (AR-97Q Tg/ À , Hsf-1 À / À ) mice were not obtained, presumably owing to their early death during embryonic development, we performed immunohistochemistry on various tissues from wild-type…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To clarify whether low expression levels of Hsf-1 have a causative role in the accumulation of pathogenic AR in vivo, we depleted Hsf-1 in AR-97Q mice by crossing them with heterozygous Hsf-1-knockout mice 33 . As Hsf-1-null AR-97Q (AR-97Q Tg/ À , Hsf-1 À / À ) mice were not obtained, presumably owing to their early death during embryonic development, we performed immunohistochemistry on various tissues from wild-type…”
Section: Resultsmentioning
confidence: 99%
“…The present study also demonstrated the neuroprotective effects of the exogenous HSF-1 in the CNS of SBMA model mice. By contrast, the depletion of Hsf-1 shortens the lifespan of a mouse model of HD, although the associated histopathological and biochemical alterations were not thoroughly examined 33 . Taken together, our findings indicate that the Hsf-1-Hsp70 pathway exerts neuroprotective effects via the suppression of pathogenic protein accumulation in the pathogenesis of polyglutamine-induced neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both increased levels of HSF1 expression and activation have been correlated with more aggressive forms of human cancer, and HSF1 has consequently been proposed as an attractive therapeutic target for cancer (Whitesell and Lindquist 2009;Santagata et al 2011;Dai et al 2012). Moreover, recent studies have revealed that HSF1 regulates transcriptional targets that extend well beyond the induction of classical HSP genes, these include IL-6, MDR-1, NFATc2 and CXCL8/IL-8, with gene expression microarray and ChIP analysis providing evidence for many more (Maity et al 2011;Singh et al 2008;Vilaboa et al 2000;Page et al 2006;Hayashida et al 2010;Trinklein et al 2004). Consistent with its broad transcriptional landscape, HSF1 is known to have a diverse range of physiological functions, including the modulation of cell migration, inflammatory and metabolic pathway regulation (Ianaro et al 2001;O'Callaghan-Sunol and Sherman 2006;Dai et al 2007;Xiao et al 1999).…”
Section: Introductionmentioning
confidence: 99%